UJI EFEKTIVITAS ANTIBAKTERI EKSTRAK DAUN SIRSAK (ANNONA MURICATA LINN.) TERHADAP BAKTERI PROPIONIBACTERIUM ACNES - Zai, Yurlina; Kristino, Agnes Yohana; Ramadhani Nasution, Sri Lestari; Natali, Oliviti (BIOLINK : Jurnal Biologi Lingkungan, Industri dan Kesehatan, 2019)
This research aims to determine the effectiveness of the antibacterial soursop leaf extract (Annona muricata L.). The method used is the agar diffusion method. The leaves were extracted by maceration method, using ethanol as a solvent. The soursop leaf extract obtained was then diluted using ethanol 96% at a concentration of 20%, 40%,60%, 80%. Positive control using clindamycin and negative controls using sterile aquadest. The research model used in this study is an experimental research model In Vitro of type. The results showed that soursop leaf extract had antibacterial effectiveness against Propionibacterium acnes with an average inhibition zone diameter of 9,7 mm; 13,7 mm; 15,7 mm; 16,3 mm; positive control (clindamysin) 21,0 mm; and negative control (aquadest) have no value tobe able to inhibit bacterial growth.